Food Studies in Latin American Literature : Perspectives on the Gastronarrative - Miseres, Vanesa; Aguila, Rocío del, 1975- (Book collections on Project MUSE., 2021)
"Collection of essays analyzing a wide array of Latin American narratives through the lens of food studies"--